Cell cycles during early steps of amphibian embryogenesis: A review. (November 2018) - Desnitskiy, Alexey G.
Abstract: The published data on cell cycles during the initial (pregastrular) period of embryonic development in representatives of the class Amphibia have been critically discussed. We have also used the literature data on ontogenetic diversity of these animals. The relatively small eggs of two principal model species for amphibian embryology, the Mexican axolotl and the African clawed frog, undergo the extensive series of rapid synchronous cleavage divisions, after which the midblastula transition (MBT) takes place: the rate of divisions slows down, the cell synchrony is lost, and the initiation of major transcriptional genomic activation occurs. However, many amphibians (including the basal species) are characterized by large, yolky, and slowly cleaving eggs with very short series of synchronous divisions. There is no reason to suggest the occurrence of the MBT in this case. The cleavage pattern in Ambystoma mexicanun (Caudata) and Xenopus laevis (Anura) represents a homoplasy and so the MBT, which is characteristic of the two model species, might have evolved convergently in these two amphibian orders as embryonic adaptations to lentic water habitats. This assumption about the convergent evolution explains some interspecific differences in the cytophysiological data on pregastrular embryos of the Mexican axolotl and the African clawed frog.